Putting pressure by patients and their families on nurses’ attitude and behaviour – fact or illusion? - Kapała, Wojciech; Konieczny, Anna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2007)
Aim: The purpose of the work was to study the phenomenon of patients and their families influencing nurses’ attitude and behaviour. Material and methods: The research was carried out on a group of 98 female and male nurses in 2005. They had worked for at least two years. Results: The results show that patients and their families frequently exert an influence on nurses and that the phenomenon is associated with giving material benefits by patients and their families or admonishing nurses. Conclusions: The results show that patients and/or their families influence the majority nurses’ attitudes and behaviours. Almost all nurses have observed the phenomenon of influencing nurses’ work among their colleagues from work.